Model Kampanye Politik Berbasis Silaturahim Bagi Calon Anggota Dewan Incumbent dalam Pemilu Legislatif 2014 - Bono Setyo (ETTISAL : Journal of Communication, 2016)
AbstractA political campaign is an event political maneuvers to draw as much as possible voters so could achieve power. Therefore every way may worn from start granting promises grandiloquence until intimidation in hope to rule. Changes to the election Ordinances will also change the ways and approach to political campaigns that are run by each of the members of the legislature. The campaign by means of political lobbying to community leaders (key person) is more preferred because it can be magnetic voice, besides the introduction of the candidate to the community through political campaigns involving society as the main way to attract attention and votes of the constituents that local community. Based on the research that has been done then it can be taken as conclusions to answer the problem formulation in this study as follows: the Model of political Campaign prospective members of the legislature include: phase identification, legitimacy, Participation Phase Phase, phase penetration and Distribution Stage. The parliamentary candidates will make use of existing media for political campaigns through print, electronic media and out-door. Political Campaign prospective Model Legislative-based friendship among others through communication channels: Group, Public communication channels, the Channels of social communication, Interpersonal, communication channels and Traditional Communications Silaturahim